El comercio según Platón: ¿factor de división o de comunidad política? - Helmer, Etienne (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
“Commerce according to Plato: a factor of division or political community?”. It is often thought that the Greek philosophers despise both wholesale trade between cities as retail trade within cities. According to this lengthy interpretive tradition, Plato conforms on this matter to Homeric and Hesiodic poetry: commerce has a reputation as a trade associated with dishonesty and profit-seeking, for which it is believed to promote more division and conflict than harmony and social cohesion. However, a careful reading of some passages in Plato’s Dialogues, and particularly of the Republic, reveals another aspect of his approach to commerce and its influence on the cohesion of the polis. Trying to highlight an aspect that is usually ignored by most interpreters, this paper argues that Plato sees in commerce itself a factor allowing the formation and maintenance of the community of the polis. This approach is based on Plato’s conviction that the political character of the human being is forged through multiple exchanges, among which trade plays a fundamental role.

Suele pensarse que los filósofos griegos desprecian tanto el comercio al por mayor entre las ciudades, como el comercio al por menor dentro de las ciudades. De acuerdo con esta larga tradición interpretativa, Platón se conforma a la poesía homérica y hesiódica al respecto: el comercio tiene la reputación de ser un oficio asociado con la deshonestidad y el afán de lucro, por lo cual se estima que propicia más la división y el conflicto que la harmonía y la cohesión social. Sin embargo, una lectura minuciosa de algunos pasajes de los Diálogos de Platón, y particularmente de la República, revela otra vertiente de su acercamiento al comercio y su influencia sobre la cohesión de la pólis. Intentando resaltar un aspecto que suele ser ignorado por la mayoría de los intérpretes, se propone demostrar en este artículo que Platón ve en el comercio en sí mismo un factor que permite formar y mantener la comunidad de la pólis. Esta apreciación reposa en la convicción de Platón en que el carácter político del ser humano se forja a través de múltiples intercambios, entre los cuales el comercio juega un papel fundamental.
“Commerce according to Plato: a factor of division or political community?”
Keywords: Trade; Economy; interchange; Plato; Republic; Comercio; Economía; Intercambio; Platón; República; https://purl.org/pe-repo/ocde/ford#6.03.01